DETERMINATION OF IN VITRO RESPONSES OF TURKISH BARLEY CULTIVARS TO PRESENCE OF ALUMINIUM - E. B. Buyukunal Bal; A. Alkus (Journal of Animal and Plant Sciences, 2011)
Aluminium (Al) is a limiting factor for plant growth in acidic soils due to its toxic property under acidic conditions. Highest Al sensitivity of barley among other cereals is important for cultivation of this crop. In this study, in vitro responses of four Turkish barley cultivars to presence of Al were analyzed based on the changes in root length, shoot length, pH of growth medium and eriochrome cyanine R staining. All cultivars were grown in MS medium with agar containing different Al concentrations (0, 10, 20, 40, 60, 80, 100 µM). Average root length measurements obtained daily over 6 d periods showed that variations in lengths were present up to 60 µM Al. However, root lengths were decreased numerically for all cultivars at 80 µM Al. Based on the root growth inhibition level at an increase of Al concentration from 60 to 80 µM, a numerically lowest root growth inhibition was observed for Konevi-98 (37.6 vs. 33.4 mm). Therefore, Konevi-98 was determined as the most tolerant variety, while Kıral-97 (32.3 vs. 29.9 mm) was followed by Konevi-98. Beyşehir-98 (31.5 vs. 21.4 mm) and Karatay-94 (31.3 vs. 23.8 mm) were determined as the most sensitive cultivars. In accordance with the root growth inhibition results, Konevi-98 had the highest shoot growth (97.3 mm; P< 0.05) and caused the least pH change (4.32; P< 0.05) on the growth medium. On the other hand, eriochrome cyanine R staining results of roots grown under various Al concentrations was not definitive for the separation of cultivars based on Al tolerances.
Keywords: barley; aluminium tolerance; root growth; pH of medium.